Penerapan Fungsi Manajemen Lembaga Cerdas Al-Quran di Bandung Barat - Virgions, Nicolous; Sanusi, Irfan; Yuliani, Yuliani (Tadbir: Jurnal Manajemen Dakwah, 2023)
Management is an activity that includes planning, organizing, implementing and controlling. So a good management in the management of the institution is very important because in the development process of an institution can be seen from planning, organizing, implementing and supervising it. The Al-Quran Smart Institute is a da’wah institution that is engaged in reading the Al-Quran. The purpose of this research is to find out the planning, organizing, implementation, and supervision in implementing the management functions of the Al-Quran Smart Institute. The theory used in this research is management theory by George Terry. The results of this study show that the Al-Quran Research Institute (LCA) in West Bandung Regency always does its best to improve the quality of the people. The planning carried out by the Al-Quran Smart Institute to improve the quality of the ummah is well done, structured and systematic. Organizing consists of division of labor, grouping and division of tasks and authority. So that with limited human resources can be maximized. Implementation is done by realizing the program that has been planned. Supervision using direct supervision method. Aims to know the condition of the field.